2015
DOI: 10.1175/waf-d-15-0021.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison and Combination of Regional and Global Ensemble Prediction Systems for Probabilistic Predictions of Hub-Height Wind Speed

Abstract: The objective of this paper is to compare probabilistic 100-m wind speed forecasts, which are relevant for wind energy applications, from different regional and global ensemble prediction systems (EPSs) at six measurement towers in central Europe and to evaluate the benefits of combining single-model ensembles into multimodel ensembles. The global 51-member EPS from the European Centre for Medium-Range Weather Forecasts (ECMWF EPS) is compared against the Consortium for Small-Scale Modelling’s (COSMO) limited-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…Junk et al . () examined the skill of probabilistic forecasts of 100 m wind for short‐range wind energy prediction based on a combination of regional and global ensemble forecasts. They also used postprocessing techniques to construct a probabilistic forecast and they found that such combinations of forecasts can considerably improve the skill when the correlation of the errors among the different ensembles is low.…”
Section: Introductionmentioning
confidence: 99%
“…Junk et al . () examined the skill of probabilistic forecasts of 100 m wind for short‐range wind energy prediction based on a combination of regional and global ensemble forecasts. They also used postprocessing techniques to construct a probabilistic forecast and they found that such combinations of forecasts can considerably improve the skill when the correlation of the errors among the different ensembles is low.…”
Section: Introductionmentioning
confidence: 99%
“…The binned-spread skill diagram compares the standard error (e.g. RMSE) of ensemble mean over binned ensemble spread and therefore is able to assess the statistical consistency at a particular forecast lead time (Junk et al, 2015). The 1:1 diagonal line of the diagram represents the perfect spread-skill line and good statistical consistency.…”
Section: Metrics To Assess Probabilistic Forecastsmentioning
confidence: 99%
“…Data from Cabauw tower have been used in a vast number of meteorological studies (Monna and Van der Vliet, 1987;Ulden and Wieringa, 1996;Durañona et al, 2007;Baas et al, 2010;Sofiev et al, 2010;Van de Wiel et al, 2010;Monahan et al, 2011;He et al, 2012;Van de Wiel et al, 2012;Drechsel et al, 2012;Monna and Bosveld, 2013a;Junk et al, 2015;Baas et al, 2016;Gualtieri, 2016;Frieß et al, 2016;Román-Cascón et al, 2016; more than 200 peer-reviewed papers), as well as in many research projects and reports (see Monna et al, 2012;Monna and Bosveld, 2013b for more references). The above articles used the data for various research purposes such as the investigation of extreme non-synoptic winds, atmospheric stability, nocturnal low-level jets, atmospheric chemistry, and wind energy studies.…”
Section: Introductionmentioning
confidence: 99%